O que o jornalismo pode ser : a expansão das fronteiras do jornalismo pós-industrial - Fontoura, Marcelo Crispim da (2020)
This thesis deals with the transformations of journalism with the expansion of its borders in a post-industrial setting. With an increasingly complex ecosystem of actors and practices, the definitions of the profession are more fluid, rejecting the duality of something being or not journalism. This thesis focuses, therefore, on what journalism can be in a digital and postindustrial context, doing so in a case study of boundary-work, with the North American consultancy Hearken. The in-depth discussion of an initiative located on the boundaries addresses the following research questions: how does the nature of organizations beyond journalism, such as Hearken, impact the expansion of journalism's boundaries?; how do the activities and skills of journalists working on an initiative beyond journalism relate to the expansion of journalism's boundaries?; how initiatives beyond journalism, such as Hearken, impact the post-industrial journalism ecosystem? To this end, this study has as main method an observation at the company's headquarters in Chicago for ten days, accompanied by interviews with employees, a group workshop and document analysis of company materials. As a theoretical framework, it relies on the concepts of beyond journalism (DEUZE and WITSCHGE, 2020) and post-industrial journalism (ANDERSON et al., 2013) to characterize the dynamism of contemporary journalism. For discussions about the historical and current nature of journalism, Ryfe (2012), Deuze and Witschge (2015; 2016; 2020), Deuze (2005; 2006; 2008a; 2008b), Kantola (2016), Traquina (2018), and Schudson (2011) are used, in addition to the notion of field by Bourdieu (1977). A characterization of journalism as a complex system is also applied, based on Morin (2015; 2016), Luhmann (1996), Erdi (2008), Urry (2005; 2005b), Nowotny (2005) and Mitchell (2009). To address journalism as belonging to the system of professions and connected to boundary work, Abbott (2014), Gieryn (1983, 1999), Carlson (2015), Coddington (2015), Singer (2015), among others, are followed. It is clear that Hearken represents the expansion of several boundaries in journalism, something visible both at the company level and among its employees and their skills and activities. It was observed the differentiation between creator and enabler of journalism, with an extension of acting space for the latter. This is a demonstration of the expansion of boundaries of the field, which doesn’t always have a clear vision of itself. The study also proposes the emergence of initiatives called interpioneer. These actors have similarities with interlopers (ELDRIDGE, 2014) and pioneer journalism (HEPP and LOOSEN, 2019), but with distinct characteristics. An interpioneer seeks to influence journalism and its audience through indirect impact with auxiliary actions, from a community of experimental practices, while questioning the definition of "journalism" and "journalist".